2021
DOI: 10.1111/jgs.17481
|View full text |Cite
|
Sign up to set email alerts
|

An implementation science approach to geriatric screening in an emergency department

Abstract: Background: The Geriatric Emergency Department (ED) Guidelines recommend screening older adults during their ED visit for delirium, fall risk/safe mobility, and home safety needs. We used the Consolidated Framework for Implementation Research (CFIR) and the Expert Recommendations for Implementation Change (ERIC) tool for preimplementation planning. Methods: The cross-sectional survey was conducted among ED nurses at an academic medical center. The survey was adapted from the CFIR Interview Guide Tool and consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 34 publications
1
28
0
Order By: Relevance
“…Their study builds on and confirms previous work that examined nursing barriers to delirium screening implementation [3]. In addition, Southerland et al undertook a survey that evaluated potential barriers to implementation of geriatric screening using the Consolidated Framework for Implementation Research and the Expert Recommendations for Implementation Change tool [4]. In their study, they identified similar barriers but also described potential strategies to address them.…”
supporting
confidence: 52%
“…Their study builds on and confirms previous work that examined nursing barriers to delirium screening implementation [3]. In addition, Southerland et al undertook a survey that evaluated potential barriers to implementation of geriatric screening using the Consolidated Framework for Implementation Research and the Expert Recommendations for Implementation Change tool [4]. In their study, they identified similar barriers but also described potential strategies to address them.…”
supporting
confidence: 52%
“…Incorporating delirium screenings into routine ED environments is challenging. 11,12 Optimizing information technology systems to support clinicians in performing geriatric screenings is an important consideration for their successful implementation. 11,13,14 Uptake of evidence-based guidelines for ED delirium screening has been limited.…”
Section: Background and Significancementioning
confidence: 99%
“…To create interventions with the optimal potential for scale-up via implementation science, future emergency medicine research including PLWD will need to investigate real-world settings with disruptive, pragmatic innovations. 21,22 Transforming geriatric emergency care for a cognitively frail population will require rational adaptations to research methods and more transparent inclusivity. A patient-centered focus on appropriate autonomy and maintaining functional capacity aligns with representative stakeholder's priorities.…”
Section: Balancing Inspiration With Pragmatismmentioning
confidence: 99%